2019
DOI: 10.1093/ofid/ofz237
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Transplacental Transfer of Antimalarial Antibodies in Kenyan HIV-Exposed Uninfected Infants

Abstract: Background Altered neonatal immune responses may contribute to the increased morbidity observed in HIV-exposed but uninfected (HEU) infants compared with HIV-unexposed uninfected (HUU) infants. We sought to examine the effects of prenatal HIV and malaria exposure on maternal and neonatal plasma cytokine profiles and transplacental antibody transfer. Methods Forty-nine HIV+ and 50 HIV- women and their HIV-uninfected neonate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 46 publications
1
27
3
Order By: Relevance
“…Some studies also found a negative effect on Hib [27, 40, 51] that is not appreciated in our study (although we found reduced IgG1 levels in cord in univariable analyses). However, our results differ from other studies that did not find any effect of HIV status on IgG levels against C. diphtheriae [36] , C. tetani [31, 36], S. pneumoniae [53], HBV [36] and measles [31, 36].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Some studies also found a negative effect on Hib [27, 40, 51] that is not appreciated in our study (although we found reduced IgG1 levels in cord in univariable analyses). However, our results differ from other studies that did not find any effect of HIV status on IgG levels against C. diphtheriae [36] , C. tetani [31, 36], S. pneumoniae [53], HBV [36] and measles [31, 36].…”
Section: Discussioncontrasting
confidence: 99%
“…Placental malaria (PM) has been shown to reduce transplacental transfer of antibodies against tetanus, measles, Streptococcus pneumoniae ( S. pneumoniae ), herpes simplex virus type 1 (HSV-1), RSV and varicella-zoster virus (VZV) [26, 31–33]. However, other studies have shown no impact of PM on transplacental transfer of tetanus, S. pneumoniae, Haemophilus influenzae type b ( Hib ), diphtheria, measles or RSV antibodies [31, 33–36]. The effect of maternal HIV infection is also controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used samples and clinical data collected by the Chulaimbo Antenatal Postnatal (CHAP) study, a prospective cohort study conducted in Kisumu, Kenya between 2011 and 2015. Details of this cohort have been described elsewhere [12,13]. Brie y, the study enrolled pregnant women aged 18-45 years presenting for antenatal consultation at Chulaimbo County Hospital (CCH).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate whether genetic variants in IFN-λ4 play a role in P. falciparum and upper respiratory tract infection frequency, we analyzed clinical data collected from 122 children that were part of a previously described birth cohort based in Western Kenya where malaria transmission is holoendemic [12,13]. The demographics of this study population, including child gender, birth weight and median number of clinical visits that they had during the 2-year follow-up are described in Table 1.…”
Section: Characteristics Of Study Populationmentioning
confidence: 99%